Fascist past, present and future? The multiple usages of the Roman Empire in Mussolini’s Italy - Corduwener, Pepijn (Incontri. Rivista europea di studi italiani, 2014)
Review of: Jan Nelis, From ancient to modern: the myth of romanità during the ventennio fascista: The written imprint of Mussolini’s cult of the ‘Third Rome’, Brussels/Rome, Belgisch Historisch Instituut te Rome/Institut Historique Belge de Rome, Brepols, 2011, 242 p., ISBN 9789074461740. € 35,00.